Prevalence of rectovaginal group B streptococcus (GBS) among pregnant women at University College Hospital, Ibadan, Nigeria. (2016)
Context: Group B Streptococcus (GBS) or Streptococcus agalactiae, a Gram-positive bacterium causes disease primarily in infants, pregnant or postpartum women. It is associated with up to 50% neonatal mortality and significant morbidity. GBS is responsible for adverse pregnancy outcomes such as premature rupture of membranes(PROM), preterm labour, low birth 'eight and chorioamnionitis. Objectives: To determine the prevalence of CBS carriage among pregnant women and identify the risk factors for colonization. Study Design: This is a prospective cohortstudy in which two hundred and forty consenting pregnant women were screened for GBS from 35 - 40 weeks. ""Vaginal and rectal swab specimens were collected from the mothers and examined using standard bacteriological methods -CHROMagar StreptB agar plate (CHROMagarLtd, Paris, France). All GBS positive isolates were tested for antibiotic sensitivity. Results: The prevalence of vaginal and rectal GBS colonization among pregnant women in University College Hospital (UCH), Ibadan was 9.6%. 0f the 23 pregnant women with GBS colonization, 60.9% (14) were vaginal cartiers,30.4% (7) were rectal carriers while 8.7% (2) had both. GBS colonization is significantly associated with previous Preterm birth, abnormal vaginal discharge in current preenancy and preterm PROM but not with maternals sociodemographic characteristics: age, parity and gestational age. Conclusion: GBS colonization of vagina and rectum has potential risks for pregnant women and their neomates. These call for screening of women during pregnaney so as to offer intrapartum antimicrobial prophylaxis to those who are carriers.